Does mode of delivery alters the perinatal outcome in uncomplicated monochorionic diamniotic twin gestation (MCDA) in comparison to dichorionic diamniotic twin gestation (DCDA): 5 year data. (7th June 2011) - Mehta, M; Cornthwaite, K; Sau, A
Abstract : Aims: To compare the mode of delivery and perinatal outcome in monochorionic diamniotic twin gestation (MCDA) twins with dichorionic diamniotic twin gestation (DCDA) twins after 26 weeks gestation. Methods: Delivery and neonatal outcome data was retrieved from medical records of 227 sets of DCDA twins and 36 sets of MCDA twins (2003–2008). Results: Data from 16 sets of twins in DCDA and two sets of twins in MCDA group could not be analysed. Outcome measures were compared between 211 pairs of DCDA twins with 34 pairs of MCDA twins. The caesarean section rates for DCDA twins was higher than MCDA twins (68.2% vs 52.9%) p<0.05. in comparison the rate of vaginal delivery was higher in MCDA twins (47.1% vs 31.8%) p<0.05. The admissions to neonatal intensive care (NICU) were more likely with MCDA twins (52.9% vs 27.0%in DCDA twins). Of the 16 twins sets in uncomplicated MCDA group delivered vaginally there were 6 admissions (37.5%) to NICU. In contrast out of 18 twins sets in LSCS group of MCDA, there were 12 NICU admissions. In 67 sets of DCDA twins delivered vaginally, 17 (25.3%) had NICU admissions. Conclusion: Mode of delivery in otherwise uncomplicated monochorionic diamniotic pregnancy has generated considerable debate in recent years. Although widely practiced, elective preterm delivery in this group is not supported by robust evidence. Further the data for vaginal birth in MCDA twins is still quite limited. Our 5 year data supports the view that mode of delivery in uncomplicated MCDA twins should not be different from DCDA twins.